2021
DOI: 10.1016/j.acra.2020.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Static and Dynamic Fractional Amplitude of Low-Frequency Fluctuation and its Prediction of Clinical Dysfunction in Patients with Diffuse Axonal Injury

Abstract: Rationale and Objectives: Recently, advanced magnetic resonance imaging has been widely adopted to investigate altered structure and functional activities in patients with diffuse axonal injury (DAI), this patient presumed to be caused by shearing forces and results in significant neurological effects. However, little is known regarding cerebral temporal dynamics and its predictive ability in the clinical dysfunction of DAI. Materials and Methods: In this study, static and dynamic fractional amplitude of low-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
(31 reference statements)
1
11
0
Order By: Relevance
“…Previous studies reported cerebellar atrophy in patients with TBI (Drijkoningen et al, 2015;Spanos et al, 2007) and lower activation within the cerebellum (Yang et al, 2012). Our previous work also showed that patients with TAI exhibited signi cantly reduced static fractional amplitude of lowfrequency uctuations (fALFF) in the left posterior lobe of the cerebellum (Zhou et al, 2021) and reduced interhemispheric coordination between the cerebellum posterior lobes (Li et al, 2017). Furthermore, analysis of the relationships between graph metrics and clinical measures showed that the nodal clustering coe cient of the right cerebellar hemisphere (VII) was negatively correlated with the MMSE score, suggesting a correlation with cognitive disorders in patients with TAI.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies reported cerebellar atrophy in patients with TBI (Drijkoningen et al, 2015;Spanos et al, 2007) and lower activation within the cerebellum (Yang et al, 2012). Our previous work also showed that patients with TAI exhibited signi cantly reduced static fractional amplitude of lowfrequency uctuations (fALFF) in the left posterior lobe of the cerebellum (Zhou et al, 2021) and reduced interhemispheric coordination between the cerebellum posterior lobes (Li et al, 2017). Furthermore, analysis of the relationships between graph metrics and clinical measures showed that the nodal clustering coe cient of the right cerebellar hemisphere (VII) was negatively correlated with the MMSE score, suggesting a correlation with cognitive disorders in patients with TAI.…”
Section: Discussionsupporting
confidence: 53%
“…However, not all compensatory activities are meaningful. Increased temporal variability may also indicate the temporal abnormity and instability in the resting state (60), causing a decline in the ability of the associated brain regions to participate in the normal cognitive loop. As the brain adapts, the compensation decreases later.…”
Section: Discussionmentioning
confidence: 99%
“…Lai CH, et al [28] 2015 Pure major depressive disorder Wang JJ, et al [29] 2016 Migraine Fang JW, et al [30] 2020 monocular blindness Shu Y, et al [31] 2020 Young depressed patients Zhou F, et al [32] 2020 diffuse axonal injury ance of fALFF in the near future. We found that fALFF value in bilateral inferior temporal lobes, right rectus, and left superior and right middle frontal lobes were increased in MOG-lgG ON patients compared to HCs, indicating that visual information processing was affected.…”
Section: Author Year Diseasementioning
confidence: 99%
“…In other dieases, fALFF method was also used to have further results (Table 5, Ref. [28][29][30][31][32]). We use the method of fALFF to study the brain activity of patients with MOG-lgG ON Change, so as to achieve early detection of related complications and sequelae brain area abnormal fALFF signal prompts, to achieve timely detection and treatment, which is essential to improve quality of patients' daily life.…”
Section: Author Year Diseasementioning
confidence: 99%